2015
DOI: 10.1080/17439884.2015.1102744
|View full text |Cite
|
Sign up to set email alerts
|

Technology, time and transition in higher education – two different realities of everydayFacebookuse in the first year of university in the UK

Abstract: This document is the author deposited version. You are advised to consult the publisher's version if you wish to cite from it. STIRLING, Eve (2015). Technology, time and transition in higher education : two different realities of everyday Facebook use in the first year of university in the UK. Learning, Media and Technology, 41 (1), 100-118. Published version Copyright and re-use policySee http://shura.shu.ac.uk/information.html Sheffield Hallam University Research Archivehttp://shura.shu.ac.uk 1 Technology, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 29 publications
0
4
0
2
Order By: Relevance
“…In this regard learners should be motivated to create Facebook group which will make them habituated of using this for reading, writing and sharing academic content. Instead of present malpractices, in this way the total Facebook Culture should be changed which make them scholar and creative as most of the developed societies' student practicing (Manca and Ranieri, 2016;Stirling, 2016). Moreover, from recent study Davidovitch and Belichenko (2018), it is clearly found and most of the scholars agreed that Facebook is a great blessing for making the learners creative and productive but it has also a dark side which should be addressed strictly particularly in case of my college students.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard learners should be motivated to create Facebook group which will make them habituated of using this for reading, writing and sharing academic content. Instead of present malpractices, in this way the total Facebook Culture should be changed which make them scholar and creative as most of the developed societies' student practicing (Manca and Ranieri, 2016;Stirling, 2016). Moreover, from recent study Davidovitch and Belichenko (2018), it is clearly found and most of the scholars agreed that Facebook is a great blessing for making the learners creative and productive but it has also a dark side which should be addressed strictly particularly in case of my college students.…”
Section: Discussionmentioning
confidence: 99%
“…This study contributes to these aspects of the field of first year university success. Stirling (2016) using a connected ethnographic approach showed how Facebook is broadly a part of being a university student and the study reported here looks to make connections between the use of Facebook and a university's role in a student's becoming. Gale and Parker (2012) suggest that in student transition success research there is a gap that is based on the understanding that first year transition is about becoming.…”
Section: Introductionmentioning
confidence: 89%
“…With the growing numbers of students using social software and networking tools, we can envisage the potential of blogs (Stirling, 2016), or peer mentor systems (Edirisingha, 2009) to capture and present 'warm knowledge' about topics that are relevant for students' transition to higher education. A comments facility can make podcasts more lively (rather than their current static state as a sound file to be downloaded or to be opened from a web browser), with on-going commentary by tutors on important issues and by other students who might elaborate some of the points made in the podcasts, although this might require external moderation.…”
Section: Discussionmentioning
confidence: 99%